23 GASTRIC BYPASS AS REVISION SURGERY FOR FAILED FUNDOPLICATIONS. (17th September 2021) - Ezz, Reda
Abstract: : Laparoscopic fundoplication as anti-reflux technique has emerged and widely expanded as a cost effective alternative to life-long medical treatment in patients with gastroesophageal reflux disease (GERD). Long-term success rate ranges from 80–90% with this procedure, but side effects still exist even with experienced surgeons. Patients with a failed anti-reflux procedure are becoming a more common problem nowadays. Although most of these patients can be managed medically, still some of them will require revisional surgery. Methods: We presented our experience from January 2015 to June 2019 facing cases of failed fundoplications. 59 cases with failed fundoplication requiring revision were included in the study. Redo fundoplications were decided preoperatively or intraoperatively to be difficult or unsafe to be done for these cases. Revision surgery for these cases was done using either distal gastrectomy and RY gastro-jejunostomy (22 cases) when the hiatal dissection was not feasible or unsafe due to obscure anatomy or Truncal vagotomy and RY gastro-jejunostomy (37 cases) when the hiatal dissection was easy and feasible. Results: Laparoscopy was used in 49 cases and was successfully completed in 42cases (%) and 7conversion (%). Improvement of symptoms: Recurrent reflux or dysphagia was noted in 19 cases (32%) and complete disappeared in 26 cases (44%). One case had leak from the GJ and another one got hematemesis. Both cases were managed conservatively. Nine patient (15%) had bile gastritis with abdominal pain. Five patients (8.5%) complained of dumping symptoms. No mortality was recorded. Conclusion: RY gastro-jejunostomy for failed fundoplications is a valid, feasible surgical option when redo fundoplication is difficult to be done or if associated with possible or expected complications.